Adaptive change in temporomandibular joint tissue and mandibular morphology following surgically induced anterior disc displacement by bFGF injection in a rabbit model. Issue 2 (February 2019) - Sato, Momoko; Tsutsui, Takamitsu; Moroi, Akinori; Yoshizawa, Kunio; Aikawa, Yoshihito; Sakamoto, Hajime; Ueki, Koichiro
Abstract: Purpose: The purpose of this study was to examine the effect of injecting basic fibroblast growth factor following surgical induced anterior disc displacement in temporomandibular joints (TMJ). Materials and methods: Adult male Japanese white rabbits (n = 16; 2.0–2.5 kg; 10 weeks old) were assigned to experimental and control groups. In the experimental group, anterior disc displacement was induced in the bilateral TMJ. Recombinant human basic fibroblast growth factor (rh bFGF) 0.1 μg/1 μL aqueous solution was injected into the left retro-discal connective tissue close to the disc (ADL group), and saline alone was injected into the same site on the right (ADR group). In the control group, a sham operation without disc position change was performed in the bilateral TMJ (CR group and CL group). Four animals from the experimental (ADR and ADL) and control (CR and CL) groups were sacrificed at 1 and 12 weeks postoperatively to evaluate the mandibular morphology and computed tomographic (CT) value of the condylar head, using 3 dimensional computed tomography. Furthermore, cartilage layers and disc tissue were examined histologically. Results: Regarding CT value at the 0° site of the condylar surface, ADR showed the lowest value after 1 week (P = 0.0325). However, there were no significant differences among the 4 groups regarding CT values at the other degree sites after 1 and 12 weeks. Regarding mandibular length, ADR showed the lowest value after 12 weeks (P = 0.0079). In condylar width, ADR showed the lowest value after 1 week (P = 0.0097). Conclusion: This study suggested that surgically induced anterior disc displacement could affect condylar morphology in the early stage, and could decrease mandibular length in the late stage. However, bFGF injection into the TMJ might prevent the degenerative change derived from anterior disc displacement and inhibition of sequential mandibular growth.